Pembelajaran Kitab Khulashoh Nurul Yaqin untuk Mewujudkan Karakter Peduli Sosial - Asna Amalia Rojana; Yasin Nurfalah (Universitas Islam Tribakti Lirboyo Kediri, 2023)
This study aims to understand the material and application of learning from the Book of Khulashoh Nurul Yaqin in shaping the character of social care at Madrasah Hidayatul Mubtadi-aat Fit Tahfizhi Wal Qiro-at Lirboyo, Kediri City. Qualitative research methods are used by collecting data through interviews with teachers. The results showed that the book's material was delivered through lecture, discussion, and question and answer methods, as well as monitoring student behavior. Even though female students have studied the book, most of them are still not able to apply the character of social care in their daily life. Support from the closest people is needed to help realize the social caring character of female students, because the influence of learning this book has not been seen significantly.